The Internalization of the Racist Discourse in Ashaninka Young People - Vigil Oliveros, Nila (2017)
The aim of this article is explaining, through the Critical discourse analysis (CDA), how the racist discourse of the elites of the city of Satipo (province of the Rainforest of Peru) has penetrated and it has naturalized into the young Ashaninka students who have migrated from their communities to do their professional studies in the city.